Determining the estimated cost of project works using aggregated indicators of labor intensity. - Gritsenko О.; Zapiechna, Y.; Shevchuk, K.; Gavrilyuk, V. (Ways to Improve Construction Efficiency, 2023)
The article is devoted to the determination of the estimated cost of project works using aggregated indicators of labor intensity. The instruction on determining the estimated cost of design works of construction objects provides for the application of percentage indicators of the cost of design works to the calculation base. The cost of the calculation base is determined with the help of similar objects, or by aggregated indicators of the cost of construction per unit of measurement. The use of analog objects has a number of disadvantages, namely: limited experience and qualifications of designers, an indefinite number of comparative objects that are available in the archive of the project enterprise, the total cost of the analog object includes the cost of material resources that affect on the estimated cost of the analogue object, and accordingly on the cost of the estimated project documentation. To get rid of the presence of the specified shortcomings, it is necessary to change the basis of justification for determining the cost of project works. It was found that the basis can only be regulatory labor intensity, as it is stable and uniform for all regions of Ukraine. The authors propose to change the basis of the justification for determining the cost by arriving at the determination of the labor intensity of the analogue object using the following methodology. The methodology shows the extent to which specific values of technical and economic indicators change for homogeneous groups of housing reconstruction objects and regression equations of specific values of labor intensity for certain types of works of a similar object. The methodology was developed on the basis of normative labor intensity values of more than 30 objects of housing reconstruction. It was determined that the normative labor intensity depends on the technical and economic indicators of the objects under investigation, namely: perimeter, height, superstructure volume and base area. As a result of the study, the limits of technical and economic indicators corresponding to 3 regression models of specific values of normative labor intensity were obtained. To verify the specified methodology, an example of determining the specific labor costs of a similar object depending on the specific values of the technical and economic indicators of the new object based on the regression equations of homogeneous groups is given. According to the equations of homogeneous groups and the corresponding technical and economic indicators, a search is made for the correspondence of the technical and economic indicators of the object under study. The specified method allows you to find a quantitative estimate of the cost of project works by individual types.